PEMBATALAN PERKAWINAN KARENA ADANYA PEMALSUAN IDENTITAS MENGENAI STATUS DIRI ISTRI DI PENGADILAN AGAMA KOTA SAMARINDA (Study Kasus Putusan Nomor 1503/Pdt.G/2015/PA.Smd) - Dewi Rahmawati (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACT Normally the Religious Court Decision No. 1053 / Pdt.G / 2015 / PA.Smd . The judge granted the annulment of marriage on the grounds Petitioners feel cheated . Law No. 1 of 1974 in Article 27 paragraph ( 2 ) explains that a husband or wife may apply for annulment of marriage at the time when the course of mating the wrong idea about themselves husband or wife . One would have thought about themselves spouses mentioned in article 27 paragraph 2 of Law No. 1 of 1974 can be expanded understanding , not only his mistakes about themselves , but also including the state of the person as a fraud . The fraud here was not only done by the men, but can also be done by the female . Of the men are usually done in the form of fraudulent falsification of identity , of the women usually hide the flaws in him. Keywords : Cancellation of Marriage , Identity Fraud